Perbedaan Status Gizi dan Status Infeksi Bayi (6-11 Bulan) yang Diberi ASI Eksklusif dengan yang Diberi Susu Formula (Studi di Wilayah Kerja Puskesmas Arjasa Kabupaten Jember) [The Differences of Nutritional Status and Infection Status beetwen Exclusive B - Tri Choiratul Aminah; Leersia Yusi Ratnawati; Sulistiyani Sulistiyani (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Recently, it has been taken over by formulated milk. It can be seen from the still low level ofcoverage of breastfeed exclusive in Arjasa which amounted to 27.95%. The intake offormulated milk may affect the infant’s nutritional status as well as its infection’s status. Infantfed formulated milk very range against a disease especially of infection diseases comparedwith baby breastfeed exclusive. Infection is one factor affecting nutrition status in infants.The most commonly known form of infection to infants with formulated milk is diarrhea. Theobjective of this research is finding out the variation on the nutrition and infection status ofthe infants with exclusive breastfeed compared to those with formulated milk intake. Thisresearch is an observational analytical descriptive one, with cross sectional design. Thisresearch involves 148 sample. Nutrition status of baby measured with the measurement ofthe weight and length body, then tested by using chi-square, after that asked gen. infection,then tested by using chi-square to know the difference. The result confirms the variation onnutrition status, as shown by the p-value of 0.000 (p<0.05).Status infection status of theinfant with exclusive breastfeed and those with formulated milk intake by p-value of 0.000(p,0.05).Conclusion this research that the difference nutrition status and status infectionbetween an infant breastfeed exclusive with formulated milk.Keywords: Nutritional status, Infection status, exclusive breastfeed and formulated milk.